Ovarian hormones and eating disorders - Young, John K. (Frontiers in Psychology, 2024)
The eating disorders anorexia nervosa and bulimia nervosa are much more common in women than in men. Also, there is evidence for a role of gene mutations in these disorders. This review examines recent data about the possibility that ovarian estrogens may contribute to the symptoms of anorexia nervosa and partly account for the sex difference in incidence of this disorder. Possible mechanisms linking genes that are abnormal in anorexia to pathways that could produce abnormal responses to estrogen are also examined. In addition, recent data pointing to a role of ovarian androgens in the symptoms of bulimia nervosa are reviewed. These data may point to more effective adjustments for the therapy of these difficult to treat disorders.